The Influence of Media on Knowledge about Marriage Preparation and Family Planning in Adolescent - Ichwan, Erika Yulita; Winancy, Winancy; Herlyssa, Herlyssa; Mukarramah, Siti (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
ABSTRACT Background: The high number of marriages and divorces in Indonesia, especially in the DKI Jakarta area, is caused by a lack of readiness to marry physically, mentally, and socially to carry out family obligations together. Objective: To compare the knowledge and effectiveness of using audio-visual media and lectures on the level of knowledge of adolescents about family preparation and planning in Central Jakarta and South Sulawesi. Methods: This study used a quasi-experimental method with a cross-sectional design. The population of this research is teenagers in the area of SMAN 5 Central Jakarta and MAN 1 Makassar, the determination of the sample size is calculated using the hypothesis test formula of 2 different proportions, determining the sample by purposive sampling and getting 30 respondents each for adolescents at SMAN 5 Makassar and 30 respondents for adolescents at MAN 1 Makassar. The data were tested by statistical paired t-test and sample t-test and using the SPSS program. The results: There is an effect of audio-visual media on increasing adolescent knowledge in SMAN 5 Jakarta and MAN 1 Makassar (p = 0.00) Suggestion: This study can be used to increase the knowledge of adolescents and their partners before entering the world of marriage to understand the importance of family planning so that they can plan their life after marriage with a better and more mature so as to minimize the occurrence of divorce. Keywords: Audiovisual media, Adolescent, Family planning and preparation